The NFT phenomenon and its special connection with intellectual property: Present and future after the burst of the bubble (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The emergence of the NFT phenomenon represented a revolution in the digital art market, largely due to the possibility of individualizing works as unique copies and the traceability of commercial operations. However, as has happened with other phenomena linked to the digital world, it ended up degenerating into a commercial bubble that has finally burst. Despite this, the NFT phenomenon is still valid, so it is necessary that from the field of Intellectual Property, clear answers are given to the questions they raise, so that both authors and collectors can operate within a sufficiently clear legal framework. Likewise, it is essential to identify the risks and tools that can help protect the rights of authors and create a safe environment for the trade of this type of works.
Keywords: NFTs; blockchain; Intellectual Property; crypto-art